Media Alternatif Sebagai Bentuk Perlawanan Masyarakat Terhadap Defisit Demokrasi Media (Studi Kasus pada Pemberitaan Wadas di Media) - Clarissa Adeline; Cassie Ruth Regina S; Catharina Susy Triputranti (Lensa, 2023)
Abstract Mass media plays an important role in society as a public space. The existence of mass media should be able to create a space for discussion and aspirations for the community and be independent. However media conglomeration by elites creates a media monopoly, which in turn erodes the role of the public sphere and creates a democratic deficit in the media. Media coverage tends to favor the rulers and elites, rather than the people, as in the case of Wadas. However, alternative media is present as a form of community movement in fighting the deficit of media democracy that occurs. Therefore, this research aims to look at the position of mainstream and alternative media in reporting the Wadas case, as a critical study and solution to the democratic deficit that occurs. This research will use a qualitative approach with content analysis methods and literature studies. The results of the study show that there is a bias in media coverage that causes a media democracy deficit. However, alternative media is present as a form of counter public movement in reviving public space and media democracy. Key Words: Mass Media , Media Democracy Deficit Defisit demokrasi media, Alternative Media, Public sphere